Effect of tillage practices and deficit irrigation on corn - Lamm, F. R., author; Aiken, R. M., author; Kheira, A. A. Abou, author (Colorado State University. Libraries, 2008)
Corn production was compared from 2004 to 2007 for three plant populations (26,800, 30,100 or 33,300 plants /acre) under conventional, strip and no tillage systems for irrigation capacities limited to 1 inch every 4, 6 or 8 days. Corn yield increased approximately 10% (23 bu/acre) from the lowest to highest irrigation capacity in these four years of varying precipitation and crop evapotranspiration. Strip tillage and no tillage had approximately 8.1% and 6.4% (18 and 14 bu/acre) greater grain yields than conventional tillage, respectively. Results suggest that strip tillage obtains the residue benefits of no tillage in reducing evaporation losses without the yield penalty sometimes occurring with high residue. The small increases in total seasonal water use (< 0.5 inch) for strip tillage and no-tillage compared to conventional tillage can probably be explained by the greater grain yields for these tillage systems.
Not digitized by CSUL Digital Services.
Presented at the 2008 Central Plains irrigation conference on February 19-20 in Greeley, Colorado.